Pengaruh pengelolaan alokasi dana desa, transparansi, dan akuntabilitas terhadap pemberdayaan masyarakat Desa Siau dalam Kecamatan Muara Sabak Timur Kabupaten Tanjung Jabung Timur tahun 2021 - Irawan, Feri; Kusumastuti, Ratih; Maulana Zulma, Gandy Wahyu (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to examine how the influence of Village Fund Allocation Management, Transparency and Accountability on Community Empowerment in Siua Dalam Village, Muara Sabak Timur District, Tanjung Jabung Timur Regency. This research is a descriptive study using a quantitative approach. This study uses a saturated sample for all Siau Dalam village apparatus, totaling 100 people. The results of the test are that the management of village fund allocation, transparency and accountability have an effect on community empowerment in Siau Dalam village, Muara Sabak Timur District, Tanjung Jabung Timur Regency. The results show that for every increase in the allocation of village funds by one unit, the community empowerment variable increases by 0.067, for every increase in transparency by one unit, the community empowerment variable increases by 0.064, and for every increase in accountability by one unit, the community empowerment variable increases. of 0.192.